Connecting the potential theory to the quantum field theory - Sazdjian, H. (Condensed Matter Physics, 1998)
A constraint theory is applied to two-particle systems to construct Poincare´ invariant wave equations with interaction potentials. The latter can be determined in the quantum field theory from Feynman diagrams. Their properties are analyzed in the case of QED. The constraint theory provides a consistent means for solving the Bethe–Salpeter equation with covariant propagators. Теорія в’язей застосовується до двочастинкової системи для побудови Пуанкаре-інваріянтних хвильових рівнянь з потенціялами взаємодії. Останні можуть бути визначені у квантовій теорії поля із Фейнманових діяграм. Їхні властивості проаналізовано у випадку квантової електродинаміки. Теорія в’язей забезпечує послідовний спосіб розв’язування рівняння Бете–Солпітера з коваріянтними пропаґаторами.